ANALYZING THE IMPROVEMENT OF STUDENTS' ARABIC LANGUAGE FLUENCY AND PRONUNCIATION USING TALKPAL AI - Siti Durotun Naseha; Abdul Ghofur; Iftitaahul Mufarrihah; Rifqi Nur Ahmada; Mochammad Fauzan Azizi (Universitas Islam Negeri Mataram, 2025)
Mastering fluency and pronunciation in Arabic poses a significant challenge for students, primarily due to a lack of practice and immediate feedback. Artificial intelligence (AI) technology, such as TalkPal AI, offers an interactive solution for practicing conversation; however, its effectiveness needs to be empirically investigated. This study aims to analyze the improvement in students' fluency and pronunciation through an intervention using TalkPal AI. The research employed a mixed methods approach with a convergent parallel design. Quantitative data were obtained from oral tests (pre-test and post-test) and analyzed using N-Gain and Paired Sample T-Tests, while qualitative data were collected through open-ended questionnaires and analyzed thematically. The results indicated a significant improvement in both fluency and pronunciation, as demonstrated by a moderate N-Gain score and the rejection of the null hypothesis (H0) in the t-test. The qualitative findings revealed that this improvement was driven by the instant feedback feature, a low-pressure learning environment, and enhanced student confidence. Therefore, TalkPal AI is proven to be an effective learning tool that can comprehensively improve students' speaking competence.